The Mass Ratio of the Epiphytic Periphyton of the Nyéki-Holt-Duna - Lakatos , Gyula; Mátrai, Ildikó; Kundrát, János; Gyulai, István (Acta Geographica Debrecina Landscape & Environment series, 2016)
The knowledge of the periphytic structure is important for the fact that the composition of epiphytic periphyton indicates the ecologically different habitats, the biological state of water-quality and its changes. Plants like reed, great bulrush, saligot, pondweed, and water-rose separately were collected from the different sampling sites for the epiphytic periphyton examination. We performed the comparability of the monitoring systems based on the periphyton category (mass), the group (ash%), the type (chl-a%), and the character (AI), and we used the biological indicators to determine the ecological state. Taking into consideration the examined years and the results of the analysis of the mass and the chemical composition of the periphyton, by means of the NTPI, the overweight of the good ecological state is characteristic of the Nyéki-Holt-Danube.